Pan LF-ELISA using BmR1 and BmSXP recombinant antigens for detection of lymphatic filariasis - Abdul Rahman, Rohana (BioMed Central, 2007)
BACKGROUND: Anti-filarial IgG4 antibody has been shown to be a good marker for detection of lymphatic filaria infection. Previous studies demonstrated that anti-filarial IgG4 assay using BmR1 recombinant antigen was highly specific and sensitive for detection of brugian filariasis. For bancroftian filariasis, an equivalent assay employing recombinant antigen expressed from the ORF of SXP1 gene has been reported. In order to detect infections by all species of lymphatic filarial, BmR1 and BmSXP recombinant antigens were employed in the development of a pan LF-ELISA. METHODS: BmR1 was previously produced while BmSXP recombinant antigen was produced by cloning the ORF of SXP1 gene from a Brugia malayi cDNA library, followed by expression in a bacterial expression system. Subsequently, each of the purified recombinant antigens (BmR1 and BmSXP) and mixture of different ratios of the two antigens (1:1, 2:1 and 1:2) were tested using IgG4-ELISA with various categories of infection and normal human serum samples. RESULTS: The results showed that both recombinant antigens were highly specific (99%–100%). For detection of brugian filariasis, BmR1 antigen alone and the mixture of BmR1 with BmSXP (1:1) gave 98% sensitivity; while BmSXP antigen alone showed 84% sensitivity. For detection of bancroftian filariasis, BmSXP antigen was more sensitive (95%) than assays using either BmR1 or mixtures of the two recombinant antigens. CONCLUSION: A sensitive and specific pan LF-ELISA for detection of lymphatic filariasis was successfully developed using two adjacent wells, each separately coated with BmR1 and BmSXP.